Estabilidade da união de um adesivo universal ao esmalte hígido, erodido e desmineralizado - Ilha, Bruna Dias (2017)
Recently, new single-step self-etching adhesive systems have been getting space in the market with more versatility proposal, the so called "universal adhesive" or "multi-mode" adhesive systems. These adhesives enable the clinician to select the most appropriate protocol for each clinical situation, allowing its application in different adhesion strategies, with or without prior acid etching. In daily practice, professionals commonly deal with substrates in different conditions from which the materials were originally developed. Considering that adhesion to enamel plays an important role in the longevity of resin/dentin bonds, the presence of enamel with mineral loss in the margins of conservative tooth preparations can compromise the restorations. Performance of the universal adhesives in demineralized and eroded enamel was still little studied, despite the relevance of these substrates. The aim of this study was to compare the immediate and six month shear bond strength (SBS) of Scotchbond universal adhesive systems applied in both etching strategies, to sound, demineralized and eroded enamel. Sixty sound permanent bovine incisors will be randomly divided into 6 groups (n=10) according to: a) substrate condition: sound (SND), demineralized (DEM - pH cycling) and eroded (ERO - immersion in cola drink); and b) etching strategy: etch-and-rinse (ER) or self-etching (SE); The adhesive system was applied on enamel surfaces according to manufacturer’s recommendations and then cylinders of composite resin were obtained from filling starch tubes (internal diameter of 0,96mm) positioned over the adhesive. Six composite resin cylinders were obtained for each tooth (specimen - experimental unit). The teeth were stored in distilled water at 37 ° C. Two cylinders of each tooth were submitted to microshear test immediately and two after six months, the two remaining cylinders will be tested after one year of aging. The SBS values (MPa) were submitted to three-way ANOVA (substrate, strategy and time) and Tukey test (α = 0.05). The triple interaction was not statistically significant. The main factors "substrate" (p = 0.000) and "strategy" (p = 0.021), as well as their interaction (p = 0.008), were significant. The SBS values presented the following order: ERO> SND> DEM and the ER strategy presented significantly higher values in SND. Demineralized enamel reduces the bond strength of Scotchbond universal adhesive system, while the eroded one does not compromise the adhesive performance. Prior acid etching results in greater adhesion to sound enamel.